Conceptual modeling - ER 2011 30th International Conference, ER 2011, Brussels, Belgium, October 31 - November 3, 2011. Proceedings - Jeusfeld, Manfred; Delcambre, Lois; Ling, Tok-Wang (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 30th International Conference on Conceptual Modeling, ER 2011, held in Brussels, Belgium, in October/November 2011. The 25 revised full papers presented together with 14 short papers and three keynotes were carefully reviewed and selected from 157 submissions. The papers are organized in topical sections on modeling goals and compliance; human and socio-technical factors; ontologies; data model theory; model development and maintainability; user interfaces and software classification; evolution, propagation and refinement; UML and requirements modeling; views, queries and search; requirements and business intelligence; MDA and ontology-based modeling; process modeling; panels.